School disengagement: Its constructions, investigation and management - Atweh, Bill; Cavanagh, Rob; Bland, D.; Carrington, S. (AARE, 2007)
School disengagement, and hence its remediation can be constructed byfocusing on either side of the individual/social debate. Much research intosocial and academic factors associated with students at risk places theindividual student (or subgroups of students) as the focus of the problem andleads into remedial activities done to or on the student(s). Often students arepassive recipients of the activities that tend to reinforce their alienation andlack of agency and reinforce the very regimes that alienate them in the firstplace. Alternatively, disengagement can be constructed as a totally socialproblem of exclusion or as a ?political resistance? by students. While suchunderstanding avoids the trap of blaming the victim, students in this case, itraises the possibility of shifting the blame to the system and its institutionsrather than providing a solution to the problem affecting both the student andthe system. This paper argues for an approach to conceptualise disengagementas discursive interaction between the individual and the social. It also discussesmethodologies for research and action that are based on this discursiveinteraction between the social and the individual.